Transcranial magnetic stimulation and transcranial direct current stimulation affect explicit but not implicit emotion regulation: a meta-analysis - Qiu, Xiufu; He, Zhenhong; Cao, Xueying; Zhang, Dandan (Behavioral and brain functions, 2023)
Emotion regulation (ER) refers to the process through which people influence the occurrence, experience, and expression of emotions. It can be established in an explicit (voluntary) or implicit (automatic) way, both of which are essential for mental and physical well-being. Recent evidence has highlighted the potential of transcranial magnetic stimulation (TMS) and transcranial direct current stimulation (tDCS) targeting the prefrontal cortex (PFC) to modulate ER. However, previous studies have only evaluated the effects of TMS and tDCS on explicit ER, leaving implicit ER relatively unexplored. In this review and meta-analysis, we systematically evaluated the effects of TMS and tDCS over the PFC on the two forms of ER, using both subjective and physiological response as outcome indicators. Twenty-seven studies were included in our study. Both subjective ( Hedges’ g = − 0.20) and physiological ( Hedges’ g = − 0.65) results indicated a significant effect of TMS and tDCS targeting PFC on down-regulation of explicit ER, but not implicit ER ( Hedges’ g = − 0.04). Moreover, moderation analysis indicated that the effect of TMS and tDCS on the down-regulating of subjective experience was moderated by several factors, including stimulation method, target area, target hemisphere, and stimulation timing. Specifically, our results showed that applying TMS or targeting the right PFC, particularly the right ventrolateral prefrontal cortex, or using offline TMS and tDCS produced a larger stimulation effect on ER. In summary, these findings suggest that TMS and tDCS has a positive effect on explicit, but not implicit ER. The distinct TMS and tDCS effect on the two forms of ER help deepen our understanding of TMS and tDCS use and provide valuable insights for the development of tailored TMS and tDCS protocols for explicit and implicit regulation.